2021
DOI: 10.1155/2021/7483445
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Simulation about Gas Transport in a Dual-Porosity Tight Gas Reservoir considering Multiple Effects

Abstract: Threshold pressure gradient, gas slippage, and stress sensitivity have important effects on the production of a tight gas reservoir. But previous studies only focused on one or two of these effects. In this study, a mathematical model considering these three effects was established to describe gas transport in a dual-porosity tight gas reservoir. Threshold pressure gradient, gas slippage, and stress sensitivity are simultaneously considered in the velocity term of continuity equation which is mainly different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Based on a combination of geomechanics and flow characteristics, Li et al [28] presented the production model for triple-porosity media, taking the adsorption and desorption of gas, slip flow, Knudsen, interfacial diffusions, and stress sensitivity into account. Chen et al [29] established the mathematical model for tight gas reservoirs considering threshold pressure gradient, gas slipping, and stress sensitivity, and Xue et al [30] conducted research on tight sandstone gas reservoirs with water produced and showed that strong stress sensitivity appeared as a result and increased with the water production. Zhao et al [31], Jabbari et al [32], Samaniego and Villalobos [33], and Zhang et al [34] carried out research on the stress-sensitivity of fracture reservoirs, and Wang and Wang [35] proposed the mathematical model considering the effect of slipping and stress sensitivity in fractured gas reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a combination of geomechanics and flow characteristics, Li et al [28] presented the production model for triple-porosity media, taking the adsorption and desorption of gas, slip flow, Knudsen, interfacial diffusions, and stress sensitivity into account. Chen et al [29] established the mathematical model for tight gas reservoirs considering threshold pressure gradient, gas slipping, and stress sensitivity, and Xue et al [30] conducted research on tight sandstone gas reservoirs with water produced and showed that strong stress sensitivity appeared as a result and increased with the water production. Zhao et al [31], Jabbari et al [32], Samaniego and Villalobos [33], and Zhang et al [34] carried out research on the stress-sensitivity of fracture reservoirs, and Wang and Wang [35] proposed the mathematical model considering the effect of slipping and stress sensitivity in fractured gas reservoirs.…”
Section: Introductionmentioning
confidence: 99%